(untitled) (Anclajes, 2018)
An area of contemporary Latin American literature shows a growing interest in reviewing the experience of the defeat of armed struggle organizations established in the region since the 1960s. Within the framework of these debates, the cycle of novels made up by Historia del llanto (2007), Historia del pelo (2010) and Historia del dinero (2013), by the Argentine writer Alan Pauls, is devoted, on the one side, to dismantling the processes of subjectivation of militancy, and interrogating crystallized meanings in the discourses and politics of memory. On the other side, through the elaboration of an impersonal aesthetic of perception that assumes estrangement as a key premise, these fictions imagine alternative imbrications between life, politics and bodies starting from the investigation of the politicity of affect.